Pendapatan Usaha Pemeliharaan Sapi Bali di Kabupaten Muaro Jambi - Darmawi, Darlim (Fakultas Peternakan Universitas Jambi, 2011)
This research aims to find out the income and the Return Cost Ratio (R/C) maintenance of Bali cattle business in Muaro Jambi Regency. This research used survey methods. Object of research is the Bali cattle ranchers PMUK Program Tunas Jaya farmer groups in the Village of Kebun IX, Muaro Jambi. Respondents of this research of 11 Bali cattle ranchers who obtained the census. The analysis used is deskriptive analysis. To find out the income and Return Cost Ratio of the Bali cattle maintenance effort using the analysis of income (Rahim, 2007). Outpouring of work hours that are used in beef cattle raising activities then used his standard working hours (JKP) according to Siregar (1996). While the cost of cages and their equipments with depreciation calculation. Results showed, that the maintenance of Bali cattle from 11 respondents (100%) is still a side business, and includes a category of patterns of family farming, with cattle ownership on average 5.61 ST / breeder. In maintaining cattle ranchers are still in the average age of 43.64 years (29-65) years including labor that is still produktiv age. Based on research results that the maintenance effort of Bali cattle in Farmers Branch, Jaya can earn positive income ie the average of Rp. 4,950,953.65, -/year/farmer or an average of Rp. 412.579,47.-/ year/farmer.-. While the comparison (ratio) between revenue and expenses (Return Cost Ratio (R / C)) the income of Rp. 272,302,450, -/periode with expenditure (cost) maintenance of Rp. 218,751,550, -/periode is the ratio of 1.24. This gives the sense that every capital of Rp 100, - it will generate income of Rp 124, -